The GABA-Withdrawal Syndrome: A Model of Local Status Epilepticus - Carmen Silva-Barrat; Jean Champagnat; Christian Menini (Neural Plasticity)
The GABA-withdrawal syndrome (GWS) is a model of local status epilepticus following the interruption of a chronic GABA infusion into the rat somatomotor cortex. GWS is characterized by focal epileptic electroencephalographic discharges and associated contralateral myoclonus. In neocorticai slices obtained from GWS rats, most neurons recorded in the GABA-infused area are pyramidal neurons presenting bursting properties. The bursts are induced by white-matter stimulation and/or intracellular depolarizing current injection and correlate with a decrease of cellular sensitivity to GABA, caused by its prolonged infusion. This effect is related to a calcium influx that may reduce the GABAA receptormediated inward current and is responsible for the bursting properties. Here we present evidence for the involvement of calcium- and NMDA-induced currents in burst genesis. We also report modulatory effects of noradrenaline appearing as changes on firing patterns of bursting and nonbursting cells. Complementary histochemical data reveal the existence of a local noradrenergic hyperinnervation and an ectopic expression of tyrosine hydroxylase mRNAs in the epileptic zone.